New Regulation on Telecommunications and Over the Top Platforms in Indonesia - Ramli, Tasya Safiranita; Ramli, Ahmad M.; Hutauruk, Gabriela Madeline (Journal of Telecommunications and the Digital Economy, 2023)
Qualified telecommunication facilities and infrastructure complement the convergence of technology applications. One of the most widely used by the public is Over-the-Top (OTT) platforms. However, it raises a new problem as domestic operator service providers are aggrieved by OTT platforms that are gaining more popularity despite their unclear legal standing. The Indonesian government responded by issuing a number of regulations. This study describes the regulations governing telecommunications and OTT platforms in Indonesia as well as pointing out the consequences and challenges of the issuance of these new regulations by taking into account the conditions of the national electronic system. This study applied a qualitative method with a normative juridical approach. Data was collected through an online literature review with analytical descriptive data processing. The results of this study elucidate the four latest regulations governing the telecommunications service sector and OTT platforms. These regulations are complementary, even though digital taxes are still seen as challenges in the form of whose outcomes are considered to have not touched the Indonesian people in general. In this instance, it demonstrates that regulations are complementary, as is the case with natural law theory, and that the law adapts to social life.